Inequality and Globalization: A Review Essay - Ravallion, Martin (Journal of Economic Literature, 2018)
As normally measured, “global inequality” is the relative inequality of incomes found among all people in the world no matter where they live. Francois Bourguignon and Branko Milanovic have written insightful and timely books on global inequality, emphasizing the role of globalization. The books are complementary: Milanovic provides an ambitious broad-brush picture, with some intriguing hypotheses on the processes at work; Bourguignon provides a deep and suitably qualified economic analysis. This paper questions the thesis of both books—that globalization has been a major driving force of inequality between or within countries. The paper also questions the robustness of the evidence for declining global inequality, and notes some conceptual limitations of standard measures in capturing the concerns of many observers in the ongoing debates about globalization and the policy responses. ( JEL D31, D63, E25, F61, F63)